Implikasi Pengaturan Konglomerasi Keuangan Terhadap Sektor Perbankan di Indonesia Pasca Ditetapkannya Undang-Undang 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Keuangan - Rahmanto, Gumelar Taufik Yugo (UI Scholars Hub, 2023)
This paper focuses on the regulatory implications of financial conglomeration on the banking sector in Indonesia after Law 4 of 2023 on the Development and Strengthening of the Financial Sector. Financial conglomeration have a negative impact, which can create systemic risk in the financial sector. Therefore, the activities of financial conglomerates need to be regulated and supervised in a comprehensive and integrated manner. Through Law 4 of 2023, the Government regulates financial conglomerates and strengthens the OJK institution in conducting integrated regulation and supervision of financial conglomerate activities. With the issuance of Law 4 of 2023, it has implications for the banking sector, namely for banks that have been designated by OJK as financial conglomerates, it is mandatory to form a Financial Conglomerate Holding Company. This is different before the enactment of Law 4 of 2023, where the controlling shareholder can simply appoint one of its financial institutions to become the main entity, which is assigned to carry out the compliance activities of the financial conglomerate.